1993
DOI: 10.1111/j.1469-8137.1993.tb03858.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen relations of the sorghum‐Striga hermonthica host‐parasite association: germination, attachment and early growth

Abstract: SUMMARYThe probability of the parasitic angiosperm Striga hermonthica achieving a successful union with its sorghum host is in part dependent on the concentration of ammonium nitrate in the growth medium. Germination rates were higher with 1 mM than with 3 mM ammonium nitrate. Ammonium nitrate did not influence either the stability of active components of host root exudate, or their perception by the parasite's seed. High concentrations of ammonium nitrate did not significantly reduce the leakage of potassium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
103
2
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 107 publications
(123 citation statements)
references
References 23 publications
17
103
2
1
Order By: Relevance
“…Stimulation of parasite photosynthesis following attachment seems to be a consequence of a greater availability of reduced nitrogen; those R. minor plants which grow on nitrogen rich hosts (nitrogen fixers) have greater concentrations of leaf nitrogen and chlorophyll, and have greater lightsaturated rates of photosynthesis than those which grow on non-fixing hosts (Seel et al, 1993a). Parasites associated with nitrogen-rich hosts may thus be more autotrophic for carbon than those oti nitrogen-poor hosts (Cechin & Press, 1993), but they are presumahly still largely dependent on the host for mineral solutes.…”
mentioning
confidence: 99%
“…Stimulation of parasite photosynthesis following attachment seems to be a consequence of a greater availability of reduced nitrogen; those R. minor plants which grow on nitrogen rich hosts (nitrogen fixers) have greater concentrations of leaf nitrogen and chlorophyll, and have greater lightsaturated rates of photosynthesis than those which grow on non-fixing hosts (Seel et al, 1993a). Parasites associated with nitrogen-rich hosts may thus be more autotrophic for carbon than those oti nitrogen-poor hosts (Cechin & Press, 1993), but they are presumahly still largely dependent on the host for mineral solutes.…”
mentioning
confidence: 99%
“…These studies have shown that Striga can radically reduce host growth, and alter biomass allocation. Grain yield and stem biomass are the most severely reduced, whilst leaf and root biomass are less affected (Graves, Press & Stewart, 1989;Cechin & Press, 1993. In addition, lower rates of photosynthesis have been observed in infected cereals than in uninfected plants, under both laboratory and field conditions (Press, Tuohy & Stewart, 1987 ;Cechin & Press, 1994;Gurney, Press & Ransom, 1995).…”
mentioning
confidence: 99%
“…O/«xMy//a«f/?0, parasites may also be governed by the supply ot prior to the development of functional haustoria solutes. Positive linear correlations between nitrogen (Pate Kuo & Davidson, 1990;Smith, Dudley & supply from the host and light saturated rates of Lynn 1990) Some hemiparasitic genera are truly photosynthesis of root hemiparasites have been facult'ative and can complete tbeir life-cycle in the reported (Cechin & Press, 1993;Press et al, 1993), absence of a bost. Such occurrences are compara-and in the mistletoes there are data to suggest that tively rare in nature, but do exist, as seen in a study water use efficiency (WUE) may be controlled by of the Mediterranean hemiparasitic annual Bartsia host nitrogen supply (Schulze & Ehlennger, 1984)t rixago .…”
mentioning
confidence: 99%